Cooperative Learning Enhances Science Outcomes: Fourth Grade Study: Pengaruh Pembelajaran Kooperatif terhadap Hasil Belajar Sains: Studi pada Siswa Sekolah Dasar Kelas IV - Eli Rusdian Rismah; Nur Efendi (Academia Open, 2023)
This quantitative experimental study aims to investigate the effect of the cooperative learning model on science learning outcomes for fourth-grade elementary school students. Using a quasi-experimental non-equivalent control group design, the research involved 16 students in the control class (IV-A) and 16 students in the experimental class (IV-B). Pre- and post-tests consisting of cognitive questions were conducted to collect data. The t-test and effect size analysis were employed to determine the influence of the cooperative learning model on science learning outcomes. The results revealed a significant effect of the cooperative learning model on science learning outcomes for fourth-grade students. Furthermore, the effect size calculation indicated a large effect, suggesting the substantial impact of the cooperative learning model. This study highlights the potential of cooperative learning in enhancing science education and provides implications for educators to adopt effective instructional strategies to improve learning outcomes. Highlights: Cooperative learning model significantly improves science learning outcomes in fourth-grade elementary students. Quasi-experimental research design used to investigate the effect of cooperative learning on science learning outcomes. Findings indicate a large effect size, emphasizing the substantial impact of cooperative learning on student achievement. Keywords: Cooperative learning, Science learning outcomes, Fourth grade, Elementary school, Quasi-experimental design